Advanced fitness assessment and exercise prescription - Heyward, Vivian H. (Human Kinetics, 2010)
This new edition provides exercise scientists with the knowledge and skills needed to assess the physical fitness status of apparently healthy individuals rather than individuals who have suspected or documented cardiovascular disease